Balance and Risk of Fall in Individuals with Bilateral Mild and Moderate Knee Osteoarthritis - Khalaj, N.; Abu Osman, Noor Azuan; Mokhtar, A.H.; Mehdikhani, M.; Wan Abas, W.A.B. (Public Library of Science, 2014)
Balance is essential for mobility and performing activities of daily living. People with knee osteoarthritis display impairment in knee joint proprioception. Thus, the aim of this study was to evaluate balance and risk of fall in individuals with bilateral mild and moderate knee osteoarthritis. Sixty subjects aged between 50 and 70 years volunteered in this study. They were categorized into three groups which were healthy (n = 20), mild (n = 20) and moderate (n = 20) bilateral knee osteoarthritis groups. Dynamic and static balance and risk of fall were assessed using Biodex Stability System. In addition, Timed Up and Go test was used as a clinical test for balance. Results of this study illustrated that there were significant differences in balance (dynamic and static) and risk of fall between three groups. In addition, the main (most significant) difference was found to be between healthy group and moderate group. Furthermore, on clinical scoring of balance, the “Timed Up and Go” test, all three groups showed significant difference. In conclusion, bilateral knee osteoarthritis impaired the balance and increased the risk of fall, particularly in people with moderate knee osteoarthritis.